Escuta clínica e atitude fenomenológica no atendimento à pessoa surda: reflexões sobre um processo psicoterápico - Oliveira, Délio Henrique Delfino de (2014)
Psychology uses listening as a work resource. When it comes to psychotherapy, listening establishes communication and makes psychologist-client dialogue easier. This qualitative research aims to discuss the clinic listening in phenomenological attitude in existential-phenomenological psychotherapy with deaf people. This perspective is based on the thinking of German philosopher Martin Heidegger, who considers humane a being-with and being-in-the-world, always unveiling meanings. Regarding the deaf people, Libras is currently the natural language of Brazilian deaf people. In this new language configuration, communication occurs in a visual-spatial modality. Thus, listening and speech gain new dimensions, demanding different ways of understanding in the field of psychotherapy. To the development of this research, we present excerpts from therapeutic sessions narratives with a deaf client, interpreted in the light of Heidegger s hermeneutics. We consider that it is possible for the psychotherapist to listen to deaf people in phenomenological attitude. Such position, which does not naturalize and limit the humane, helps so that the clients do not feel responsible for their existence and can hermeneutically converse in their language. In this context, the psychologist must be qualified to conduct the treatment in Libras. We hope that this research can, somehow, fill the existing gap of the scientific production about such theme in the field of Psychology and, mainly, instigate discussion in the context of Psychology courses on the importance and need to qualify psychologists for the management of clinical practice with deaf people